Strukturalisme Genetik Lucien Goldmann dalam Novel Seporsi Mie Ayam Sebelum Mati Karya Brian Khrisna: Lucien Goldmann's Genetic Structuralism in Brian Khrisna's Novel A Portion of Chicken Noodles Before Dying - Zulham Putra Fama Alfatihi; Roziah Roziah (ITScience (Information Technology and Science), 2026)
This study aims to analyze Brian Khrisna’s novel Seporsi Mie Ayam Sebelum Mati through Lucien Goldmann’s genetic structuralism to reveal the relationships among the work’s structure, human facts, and the author’s worldview. This research is motivated by the increasing phenomenon of bullying and mental health crises among the younger generation, which are represented in literary works as a reflection of contemporary social reality. The method used is a descriptive, qualitative method with content analysis and hermeneutic techniques. The research data are in the form of words, phrases, sentences, and paragraphs in the novel, as well as supporting data from scientific literature and interviews with the author. The analysis is carried out by identifying intrinsic elements, reconstructing human facts, and systematically exploring the author’s worldview. The results show that the structure of the literary work is built coherently through existential themes, dialectical plots, representative characters, multiple conflicts, and a competitive urban social setting. The human facts found include bullying, mental health crises, and social alienation as collective phenomena of modern society. Meanwhile, the author’s worldview leads to existential humanism that emphasizes empathy, acceptance, and the meaning of a simple life. Homologically, there is a match between the work’s structure, social reality, and the collective consciousness of the younger generation. The conclusion of this study confirms that the novel not only serves as a social reflection but also critiques competitive culture and a lack of concern for mental health, while offering more humanistic values in the form of empathy and solidarity.